Angiopoietin-2 differentially regulates angiogenesis through TIE2 and integrin signaling - Felcht, Moritz; Vettel, Christiane; Kutschera, Simone; Appak, Sila; Wieland, Thomas; Goerdt, Sergij; Augustin, Hellmut (The journal of clinical investigation, 2012)
Angiopoietin-2 (ANG-2) is a key regulator of angiogenesis that exerts context-dependent effects on ECs. ANG-2 binds the endothelial-specific receptor tyrosine kinase 2 (TIE2) and acts as a negative regulator of ANG-1/TIE2 signaling during angiogenesis, thereby controlling the responsiveness of ECs to exogenous cytokines. Recent data from tumors indicate that under certain conditions ANG-2 can also promote angiogenesis. However, the molecular mechanisms of dual ANG-2 functions are poorly understood. Here, we identify a model for the opposing roles of ANG-2 in angiogenesis. We found that angiogenesis-activated endothelium harbored a subpopulation of TIE2-negative ECs (TIE2lo). TIE2 expression was downregulated in angiogenic ECs, which abundantly expressed several integrins. ANG-2 bound to these integrins in TIE2lo ECs, subsequently inducing, in a TIE2-independent manner, phosphorylation of the integrin adaptor protein FAK, resulting in RAC1 activation, migration, and sprouting angiogenesis. Correspondingly, in vivo ANG-2 blockade interfered with integrin signaling and inhibited FAK phosphorylation and sprouting angiogenesis of TIE2lo ECs. These data establish a contextual model whereby differential TIE2 and integrin expression, binding, and activation control the role of ANG-2 in angiogenesis. The results of this study have immediate translational implications for the therapeutic exploitation of angiopoietin signaling.